Contact-impact problems using a quasi-linear finite element appraoch - Faris, Waleed Fekry (INSI Publications, 2012)
Contact-impact problems are a class of problems that exist in almost all machinery, automotive, aerospace, and structural applications. The contact-impact phenomena is inherently nonlinear and numerous approaches were used to solve such problems. In this paper, we exploit the linear Finite Element formulation within an incremental approach to solve Contact-impact problems under random excitations. The random excitations were modeled using Monte-Carlo simulation. We studied the input-output relationship for some of these problems to see the effect of random excitation on structural behavior.